2008
DOI: 10.1007/s10997-008-9053-x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social reporting and board representation: evidence from the Kenyan banking sector

Abstract: Corporate social reporting, Kenya, Banks, Board representation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
376
7
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(462 citation statements)
references
References 47 publications
69
376
7
10
Order By: Relevance
“…On the other hand, Liao et al (2014) argues that as women have a different role from men in society, female directors on the board may take a different approach to environmental issues. In line with these arguments, Rupley et al (2012) (2015) and Barako and Brown (2008) found a positive a relationship between the extent of disclosure related to environmental issues and the number of women members on the corporate board. Thus the third hypothesis of the study is formulated as follows:…”
Section: Gender Diversitymentioning
confidence: 72%
See 1 more Smart Citation
“…On the other hand, Liao et al (2014) argues that as women have a different role from men in society, female directors on the board may take a different approach to environmental issues. In line with these arguments, Rupley et al (2012) (2015) and Barako and Brown (2008) found a positive a relationship between the extent of disclosure related to environmental issues and the number of women members on the corporate board. Thus the third hypothesis of the study is formulated as follows:…”
Section: Gender Diversitymentioning
confidence: 72%
“…Huse and Solberg (2006) ascertain that women may make contributions on corporate boards by creating alliances, preparation and involvement, taking part in important decisions, taking leadership roles and being visible. Barako and Brown (2008) state that an increased proportion of women on the board leads to better corporate communication. On the other hand, Liao et al (2014) argues that as women have a different role from men in society, female directors on the board may take a different approach to environmental issues.…”
Section: Gender Diversitymentioning
confidence: 99%
“…Choi et al [92] conclude that the presence of independent members on companies' boards has a positive impact on companies CSP, measured by the KEJI Index, which has scores for the following categories: (i) companies' contributions to communities; (ii) employee and consumer protection and satisfaction; (iii) firms' environmental protection; and, (iv) companies' contributions to economic growth. Barako and Brown [83] analyzed a sample of 40 Kenyan banks and provided empirical evidence of a positive influence of board independence on CSP. Focusing on the largest 100 Australian firms, Rao et al [16] found a positive relationship between board independence and CSP, measured by social and environmental disclosures.…”
Section: Linking Board Independence and Corporate Social Performancementioning
confidence: 99%
“…However, in the case of the banking sector, previous literature is scarce. As far as we know, Barako and Brown's (2008) study is unique in relation to this question; they suggest that Kenyan banks with more female directors show higher levels of CSR disclosures. Accordingly, we propose the following hypothesis that will be tested for an international sample of banks:…”
Section: Diversity Of the Board And Csr Reporting In The Banking Sectormentioning
confidence: 91%
“…2018, 8, 41 4 of 23 focused on specific regions. Concretely, Barako and Brown (2008) suggested a positive link between the board independence and CSR reporting in the Kenyan banking sector. Htay et al (2012) show similar findings in the case of Malaysian listed banks; and Khan (2010) and Sharif and Rashid (2014) did so for banks in Bangladesh and Pakistan, respectively.…”
Section: Introductionmentioning
confidence: 99%